Seasonal and latitudinal variations of surface radio refractivity over Nigeria - Modupe Enice Sanyaolu; Sanyaolu Olufemi (Institute of Advanced Engineering and Science, 2022)
Refractivity is a significant challenge of radio signal propagation. As it often distorts or leads to loss of signals. The seasonal and latitudinal variations of surface refractivity at three Nigerian tropospheric Observatory stations in Nigeria, namely Port-Harcourt, Lagos, and Makurdi, are presented in this paper. Values of monthly averages of pressure, temperature, relative humidity, and water vapour from the stations were used to compute surface refractivity at each station. The results show that the values of surface refractivity increase from the arid region in the north to the coastal area in the south. There was an increase in the values of surface radio refractivity from the minimum value of about 332.83 N-units at Makurdi station to a maximum value of 386.69 N-units at Lagos station. Seasonal variations are seen to be caused by weather conditions. The values of the surface refractivity increased significantly in the wet season and reduced in the dry season. It also shows that the values of surface radio refractivity are affected by the meteorological components mentioned above. The result of this study is needed for effective planning of good signal reception in these stations.